(untitled) (Journal of Political Science and International Relationship, 2024)
Our world has always faced numerous issues, driven by both natural cycles and the egoistic desires of states. Global organizations struggle to prevent human rights violations and environmental damage, as international structures from the early industrial era have become ineffective. A new Cold War has emerged, shifting from military to psycho-material spheres, with a focus on AI, drones, cybersecurity, and nuclear weapons. In the northwest of Eurasia, a new military intervention among Slavs is in full swing. Two forces, each stubbornly refusing to capitulate, fight against each other, raising questions about the morality of their actions. Every people, ethnicity, or nation has the right to self-determination, but these conflicts often lead to significant geopolitical tensions. Ukraine, a sovereign state, is at the heart of this global tension. It has the right to decide what is best for its people and to choose its own path of development. However, in our globalized world, every action can have far-reaching consequences, much like the "butterfly effect." Ukraine must consider the interests of its former partners and modern neighbors to navigate this complex landscape. At this critical juncture, Ukraine must reflect on its choices, asking itself: "What did we overlook?" The country’s decisions are pivotal, not only for its future but also for global stability. Every move in this geopolitical chess game has the potential to alter the balance of power, making Ukraine’s choices crucial in shaping the outcome of this new era of global relations.